Agribusiness Development Model of Domestic Chicken Commodity as Smallholder Farming in South Sulawesi Province - Hasanuddin Remmang; Herminawaty Abubakar; Tahmrin Abduh; Chahyono Chahyono (Universitas Dharma Wacana, 2022)
This study aims to obtain the results of a study on the behavior of domestic chicken agribusiness development in South Sulawesi province. The analysis model in this study uses a structural equation model to examine the relationship between variables in accordance with the proposed hypothesis. The variables studied in this study consist of exogenous variables including: production, marketing, and financial management capabilities; intermediate variables in this study are sales development; and variables of increasing business profits as endogenous variables. The three types of variables are built based on a theoretical approach that forms a constellation of relationships between variables, where each variable has dimensions and indicators. The respondents in this study were 250 managers of domestic chicken farms in Maros and Gowa districts. The results of the study found that generally respondents of domestic chicken farmers in Gowa and Maros districts have the ability of production, marketing, and financial management in increasing sales development and its impact on increasing profits. Based on the results of the study, it is expected that the chicken farming business in both districts can develop through the role of the government and related parties, so as to improve the standard of living of the community and increase the source of regional income